Tolerability of Narrow-band Ultraviolet-B Phototherapy for Different Dermatological Diseases in Relation to Co-medications - Anna M. Halupczok; Ann-Sophie Bohne; Sascha Gerdes; Stephan Weidinger; Michael Weichenthal (Medical Journals Sweden, 2024)
Phototherapy is an efficient therapy for a variety of skin diseases. Various drugs can cause photosensitivity and impact tolerability of phototherapy. The tolerability was investigated of narrowband ultraviolet-B 311 nm therapy in dependence on the underlying disease and long-term co-medication. A total of 534 narrowband ultraviolet-B therapy courses were examined. Compared with psoriasis, adverse events were observed more frequently in eczematous diseases and, in some cases, other indications. About two-thirds of all courses were carried out in patients taking at least one photosensitising drug, according to the summaries of product characteristics. Phototherapy was more frequently associated with adverse events when medication was taken concomitantly. When considering the tolerability of phototherapy in dependence on individual substances or drug classes, no statistically significant result was shown after adjustment.